(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
Exclusive breastfeeding is essential nutrition that contains white blood cells, enzymes, hormones and proteins needed for the continued growth and development of a baby’s life. One of the factors that can affect the smoothness of exclusive breastfeeding is the husband’s support. The husband’s role in the exclusive breastfeeding program is to create a comfortable and calm atmosphere for the mother so that the mother’s psychological condition is healthier and happier. The aim of the research is to find out the husband’s support in the implementation of exclusive breastfeeding.Descriptive research design, population and sample of 30 respondents, total sampling technique, questionnaire research instrument, the research was conducted on March 18 - April 8 2023. The research variable was husband’s support for exclusive breastfeeding. Data analysis uses the percentage formula and is interpreted quantitatively. The results of the study of 30 respondents showed that most of the husband’s support was sufficient, as much as 60%, and almost half of the husband’s support was good, as much as 40%. The success in giving exclusive breastfeeding has the support of the husband, by providing a safe and comfortable atmosphere and always increasing knowledge about the importance of exclusive breastfeeding,